Divergent opinions regarding appointment of academics to judicial offices in Nigeria : a socio-legal approach - Aliyu, Musa Adamu; Aliyu, Nasiru Adamu (Penerbit Universiti Kebangsaan Malaysia, 2021)
Competence of academics to become judges has attracted divergent opinions among legal scholars. Intellectually academics have been conducting researches and disseminating the findings of the works in journals. Outside the four walls of the universities, the scholars are helping courts to appreciate difficult legal issues by filing scholars’ brief. They appear before the courts as friends or amici curiae. In the United States, it is a tradition to appoint academics as judges, and there is similar practice in various parts of the world. Nigeria is one of the countries where academics were elevated to become judicial officers or judges of Superior Courts. Late Justice Teslim Elias was an academic appointed as a judicial officer. There are opinions for and against appointment of members of the academia into judicial offices. Proponents of the appointment believe that academics are suitable to be appointed as judges by virtue of their knowledge. On the other hand, those against such appointment are of the view that the academics lack practical experience in the courtroom. This reason makes them unqualified to be appointed judges. This paper has adopted a socio-legal research approach to understand the perspectives for and against appointing academics as judges. Nine members of the legal profession have been interviewed and majority of them have supported the appointment.